A simple highly selective ratiometric fluorescent probe for detection of peroxynitrite and its bioimaging applications. (February 2023) - Zeng, Xiaodan; Chen, Xin; Chen, Jie; Ma, Mingshuo; Jin, Hua; Yu, Shihua; Liu, Zhigang
Abstract: Peroxynitrite (ONOO − ), a potent oxidant, plays an important regulation role in different physiopathological processes. Its overproduction can potentially cause several diseases. Therefore, being able to accurately and selectively monitor ONOO − could help elucidate the interaction and function of ONOO − in physiological and pathological processes. Herein, a novel naphthalimide derived ratiometric fluorescent probe was successfully designed and synthesized for monitoring ONOO − in RAW 264.7 macrophage cells and zebrafish. The probe showed highly selective towards ONOO − with satisfactory sensitivity (detection limit: 0.32 μM) and a significant 15 - fold enhancement of fluorescence ratio accompanied with a large blue shift of 110 nm. In addition, further biological experimental studies showed that the probe could track ONOO − in RAW 264.7 macrophage cells and zebrafish animal models with specific sensitivity and reliability. Therefore, the probe can be expected to be a biological tool for developing the role of ONOO − in physiological systems in the future. Graphical abstract: Image 1 Highlights: A novel ratiometric fluorescent probe for ONOO − was designed and synthesized. The probe demonstrated superior selectivity and sensitivity to ONOO − . The probe revealed ONOO − in cells and zebrafish successfully.